Trials of enslavers in former French colonies in the eighteenth and nineteenth centuries: testimonies of the enslaved between gratitude and fear - Göltl, Teresa (Slavery and abolition, 2024)
This article sheds light on a rarely considered aspect of colonial reality: trials of enslavers. The focus lies on lawsuits against members of the slaveholding elite in which enslaved people appeared as witnesses. These sources represent a moment of confrontation within colonial society which allows for an exploration of power relations through the eyes of the enslaved rarely discovered so far. This article discusses some methodological issues of working with this type of source as well as considering how the testimonies can be used and analysed through the lens of the History of Emotions. Reading the testimonies, we encounter a wide range of emotions, from anger, jealousy, and fear up to relief and gratitude. Some of the enslaved defended the accused enslaver by expressing gratitude for food and medicine. Others denounced their enslaver using their testimony as a way of spelling out their grievances. Their accounts, even though highly mediated, not only show how existing legal and social structures were contested, but also how the enslaved opened up spaces of resistance to make their voices heard.